Digital Infrastructure Development Driving the Intelligent Transformation of Manufacturing: Technological Application Scenarios and Policy Optimization Strategies - Ge, Liyu; Ning, Keke; Zheng, Mengyi (Asia Pacific Economic and Management Review, 2025)
The analysis begins by deconstructing the conceptual architecture of digital infrastructure, articulating how its core components—ubiquitous connectivity, pervasive sensing, distributed computation, and integrative platforms—logically necessitate the emergence of key manufacturing capabilities such as real-time perception, data-driven cognition, adaptive response, and systemic integration. These capabilities are then logically synthesized into three representative technological application scenarios: holistic visibility and optimization, predictive intervention and autonomous quality assurance, mass customization through flexible reconfiguration. The paper further deduces the inherent socio-technical challenges that arise from this infrastructural transformation, including economic barriers, structural complexities, and skill obsolescence. Finally, through logical extension, the paper proposes a holistic set of policy optimization strategies designed not to subsidize technology adoption per se, but to cultivate a fertile ecosystem that addresses these inherent challenges, fosters innovation, and ensures the equitable and sustainable evolution of the manufacturing sector.